A conceptual framework for green entrepreneurial orientation and sustainable business performance in emerging Asian markets - Jumbri, Isma Addi; Widjajanti, Kesi; Abdul Hamid, Mohd Syaiful Rizal; Lestari, Rohmini Indah; Gilang, Puspita Rini; Bakri, Mohammed Hariri (SHPMedia Sdn Bhd, 2025)
The rise of startups in Indonesia and Malaysia highlights their crucial role in fostering sustainability, innovation, and economic resilience. However, these startups face significant challenges, including resource constraints, complex regulatory environments, and limited access to green financing. Addressing these challenges is essential for achieving a competitive advantage and fostering long-term resilience. This conceptual paper develops a theoretical framework grounded in the Resource Advantage Theory of Competition (RAToC) to explain how Green Entrepreneurial Orientation (GEO) influences Sustainable Business Performance (SBP). The study integrates Green Innovation Capability (GIC) and Positional Advantage (PA) as mediators, while Strategic Green Marketing Orientation (SGMO) acts as a moderator. By focusing on Indonesia and Malaysia, this research bridges gaps in the literature and offers practical insights for policymakers, investors, and entrepreneurs in emerging economies.